Pengaruh Penggunaan Multimedia Berbasis Komputer Terhadap Hasil Belajar Kimia Pada Materi Minyak Bumi di Kelas X SMA N 1 Indralaya - Silvia Septhiani; Jejem Mujamil S A; Rachman Ibrahim (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. The impact of using computer based multimedia to student’s chemistry achievement of crude oil topic at X class SMA N 1 Indralaya. The aims of this research to determine how different achievement between study by using computer and without using it in crude oil topic. The programme used macromedia flash 8. The method used quasi experiment. Data collection technique by test value. Test result prove experiment class in achievement. Experiment got average value 78,99 and 69,01 to control. Experiment class have passed standard value more than 85% and only 64,4% for control class. T-test significance level 5% t.count > t.table was 2,83 > 2,00. The result showed, there was significant differences between experiment class and control class. Keyword: multimedia based computer, student achievement